The Pedicled LICAP Flap Combined with a Free Abdominal Flap In Autologous Breast Reconstructions - Thomas Sjøberg, MD; Louis de Weerd, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Previous surgery or slim body configuration can limit the size of the available abdominal flap in autologous breast reconstruction. However, redundant skin and subcutaneous tissue lateral to the mastectomy site can be utilized as the pedicled lateral intercostal artery perforator (LICAP) flap. This study evaluates the combination of a free abdominal flap and a pedicled LICAP flap to achieve increased breast size and improved cosmetic outcome. Methods:. Patients undergoing secondary autologous breast reconstruction were included in a prospective study. The combination with a LICAP flap was used for women with insufficient abdominal flap tissue in relation to the desired breast size. The authors also assessed their modification of the original lateral thoracodorsal flap design to improve the aesthetic outcome. Results:. In 109 patients, 121 free abdominal flaps were performed. The combination with a pedicled LICAP flap was used in 82 free abdominal flap reconstructions (68%). The LICAP flap provided additional volume and resulted in better projection and ptosis of the neo-mamma. The overall complication rate for the LICAP flaps was 26 %; all minor complications. Despite combining flaps, the majority of patients needed additional surgery to improve breast symmetry. Breast reduction of the native breast was the most common symmetrizing procedure. Conclusion:. In selected patients with insufficient abdominal flap tissue, a combination of a free abdominal flap and a pedicled LICAP flap is a valuable option to increase breast size and cosmetic outcome. Additional symmetrizing surgery might still be necessary.